Performance Of Plate Distributor And Spray Nozzle For An Unpacked Saturator. - Adlan, M N; Tan, E W J; Aziz, H A (2004)
Saturator efficiency is vital in operational cost of dissolved air flotation plants as it would have an impact on the amount of recycle ratio required for satisfactory removal of suspended solids from the influent stream.